Grynfeltt Hernia: A Deceptive Lumbar Mass with a Lipoma-Like Presentation - Jonathan R. Zadeh; Jessica L. Buicko; Chetan Patel; Robert Kozol; Miguel A. Lopez-Viego (Case Reports in Surgery)
The Grynfeltt-Lesshaft hernia is a rare posterior abdominal wall defect that allows for the herniation of retro- and intraperitoneal structures through the upper lumbar triangle. While this hernia may initially present as a small asymptomatic bulge, the defect typically enlarges over time and can become symptomatic with potentially serious complications. In order to avoid that outcome, it is advisable to electively repair Grynfeltt hernias in patients without significant contraindications to surgery. Due to the limited number of lumbar hernioplasties performed, there has not been a large study that definitively identifies the best repair technique. It is generally accepted that abdominal hernias such as these should be repaired by tension-free methods. Both laparoscopic and open techniques are described in modern literature with unique advantages and complications for each. We present the case of an unexpected Grynfeltt hernia diagnosed following an attempted lipoma resection. We chose to perform an open repair involving a combination of fascial approximation and dual-layer polypropylene mesh placement. The patient’s recovery was uneventful and there has been no evidence of recurrence at over six months. Our goal herein is to increase awareness of upper lumbar hernias and to discuss approaches to their surgical management.